Debt sustainability under catastrophic risk: The case for government budget insurance - Eduardo Borensztein; Eduardo Cavallo; Patricio Valenzuela (Inter-American Development Bank, Research Department, 2007)
Natural disasters are an important source of vulnerability in the Caribbean region. Despite being one of the more disaster-prone areas of the world, it has the lowest levels of insurance coverage. This paper examines the vulnerability of Belize's public finance to the occurrence of hurricanes and the potential impact of insurance instruments in reducing that vulnerability. The paper finds that catastrophic risk insurance significantly improves Belize's debt sustainability. In addition, the methodology employed makes it possible to estimate the appropriate level of insurance, which for the case of Belize is a maximum coverage of US120 million per year. International organizations can play a role in assisting countries to overcome distortions in insurance markets, as well as in helping to relax internal political resistance to the purchase of insurance policies.
Keywords: H30; G15; G22; Q54; 330; Public Finance; Insurance; Natural Disasters